The Effectiveness of Acceptance and Commitment Therapy on Psychological Well-being in Men and Women with Chronic Musculoskeletal Pain - Ensandoost, Tayebeh; Samari, Ali Akbar; Bayazi, Mohammad Hossein; Rajaei, Alireza (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the effectiveness of acceptance and commitment therapy on psychological well-being of patients with chronic musculoskeletal pain. Methods: The method of the present study was quasi-experimental with pre-test-post-test design and follow-up with a control group. The statistical population of the study included all patients with chronic musculoskeletal pain in the summer of 2020 in Torbat-e-Jam, from which 30 eligible individuals were selected by convenience sampling and randomly divided into experimental and control groups (15 in each group). And answered the psychological well-being questionnaire. Were placed. Acceptance and commitment treatment was taught in eight sessions weekly. Statistical data were analyzed using repeated measures analysis of variance and SPSS-16 software at a significance level of α = 0.05. Results: The results showed that acceptance and commitment treatment significantly improved psychological well-being in the experimental group compared to the control group (P